Primary subglottic inverted papilloma: An exceptional localization - Özlem Saraydaroglu; Hakkı Caner İnan; Selin Yirmibes (Indian Journal of Pathology and Microbiology)
Inverted papillomas are predominantly seen in the sinonasal region. Extra-sinonasal lesions are considered to be heterotopic. We present a case of primary laryngeal inverted papilloma with an unusual subglottic localization. An 84-year-old female patient presented with dyspnea on exertion. In the endoscopic examination, a subglottic vegetative lesion was observed. Radiological examination revealed a well-circumscribed, solid mass involving the anterior commissure and extending to the subglottic region. Total excision of the mass was performed with the CO2 laser surgery. Histopathologic examination revealed endophytic growth of round-oval nests of transitional hyperplastic epithelium. The patient was diagnosed with primary laryngeal inverted papilloma. Primary laryngeal inverted papillomas are extremely rare. This is the fifth case and the only the second with a subglottic localization. Due to its rarity, it is difficult to predict the underlying cause and clinical course. However, cases with an atypical localization must be followed up like those in the sinonasal region.